2010
DOI: 10.1002/pssc.200982893
|View full text |Cite
|
Sign up to set email alerts
|

Intensity dependence of quantum efficiency and photo‐gating effects in thin film silicon solar cells

Abstract: Steady‐state photoconductivity measurements have been carried out on thin‐film silicon pin structures of i‐layer thickness typically 4 μm, where crystalline composition has been varied by adjustment of the silane concentration in the process gas. In amorphous and low‐crystallinity cells, strongly‐absorbed light incident from the p‐side at photon fluxes in excess of 1014 cm‐2 s‐1 produces strongly sub‐linear intensity dependence, ‘S’ shaped reverse current‐voltage curves and amplification of a second weakly‐abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…However, in case of dichromatic or multispectral illumination, the local low-field region might be offset so that the transport of electrons generated in the device front is facilitated. In result, a significantly larger amount of photogenerated electrons can drift towards the electrical contact so that collection efficiencies can exceed unity gain 27 , 29 , 33 . Such light-induced electrical field deformations enabled by photogating predominantly occur in defective materials, like a-Si:H, which exhibits a large amount of deep dangling bond states rather than localized tail states.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in case of dichromatic or multispectral illumination, the local low-field region might be offset so that the transport of electrons generated in the device front is facilitated. In result, a significantly larger amount of photogenerated electrons can drift towards the electrical contact so that collection efficiencies can exceed unity gain 27 , 29 , 33 . Such light-induced electrical field deformations enabled by photogating predominantly occur in defective materials, like a-Si:H, which exhibits a large amount of deep dangling bond states rather than localized tail states.…”
Section: Resultsmentioning
confidence: 99%
“…In a-Si:H waveguides, optical (N)AND logic gate operation in the time domain at GHz frequencies has already been demonstrated utilizing four-wave mixing Bragg scattering; a third-order nonlinear process that requires high intensity laser illumination 26 . In a-Si:H field-optimized p-i-n photodetectors and solar cells, it was found that collection efficiencies can exceed values of long-term optimized crystalline silicon photodiodes that utilize photogating in the visible range 27 29 . Compared to conventional high-temperature silicon manufacturing, the mature thin-film deposition technology of a-Si:H allows for ubiquitous sensor integration on top of read-out electronics at low temperatures and costs with pixel fill factors up to 30 , 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Further experiments have been conducted to investigate and quantify the achievable bandwidth, the responsivity gain, and the detection limit at different light levels since charge carrier collection efficiencies strongly depend on the gate and the probe illumination irradiance and its ratio [13,14,16].…”
Section: Ac Probe Modulationmentioning
confidence: 99%
“…Previous results demonstrating photon collection efficiency gains beyond unity in a-Si:H based detectors achieve rise times ranging from 10 −5 s to 0.1 s. However, such photo-gated sensors suffer from comparatively slow decay times of the photo-gated current transients resulting in time constants exceeding seconds. Furthermore, the a-Si:H p-i-n photodetectors presented in [13,14,16], invariably require extensive light soaking prior to the measurement to establish temporarily an initial low-field region within the detector. The overall bandwidth enhancement by at least one order of magnitude reported in this work can mainly be attributed to:…”
Section: Detector Bandwidthmentioning
confidence: 99%
See 1 more Smart Citation